La informalidad: propuesta de modificación del impuesto general a las ventas y del impuesto a la renta para las MYPEs - Chávez Gonzales, Ángel Marco (2020)
The mandatory social isolation by COVID-19 has impacted the growth of the economy, revealing the high rate of informality, which has hindered the State from exercising efficient control to apply sanitary measures and grant benefits. Informality is more intense in the activities of the SMEs. One of the causes is the effect that taxes have on their decisions, such as the Business Income Tax and the General Sales Tax, therefore we propose to modify the General Sales Tax and Income Tax SMEs regarding its tax incidence in order to attract the informal and informal activities to formality.